Quality Analysis of AlTi5B1 Master Alloys - Svobodova, Jaroslava; Hajdúch, Peter (Manufacturing Technology Journal, 2017)
Grain refinement in commercial aluminium alloys can be achieved by addition of AlTi5B1 master alloy, containing α aluminium matrix, TiB2 and Al3Ti particles. These particles act as nucleation points for α Al matrix, resulting in a uniform fine, equiaxed as cast microstructure. Current grain-refinement practice involves the addition of master alloy (e.g. Al-Ti-B, Al-Ti-C) before casting introducing inoculants particles to the melt. The final size SDAS in aluminium cast alloys depends on the kinetics of both nucleation and growth of solid in the liquid. As per the classical nucleation theory, the critical activation energy (ΔG*) to form stable nucleus and the critical radius (rkr.) for the nucleus to grow into a crystal with long order atomic arrangement are inversely proportional to the undercooling. In practical instances, nucleation does not occur heterogeneously on solid substrates such as mould walls. Several works, mainly regarding primary foundry alloys, have been carried out on grain refinement revealing how the TiB2 particles present in AlTi5B1 master alloy provide a germ for heterogeneous nucleation; however, these particles become efficient grain refiners only with excess Ti content. This condition can not only increase the nucleating potency of TiB2 particles, but also reduce the grain growth of primary α - Al crystals during solidification. At atomic scale the nucleating potency of TiB2 is dictated by the mismatch between the lattice of this particle and the nucleating phase. The performance of AlTi5B1, well established to be the best grain refiner for cast aluminium alloys as AlSi7Mg0.3 and AlSi12Cu2. Producer of the master alloys as AlTi5B1 guarantee the chemical composition but not size of particles that are very important for solidification process. This review focuses on the quality of five AlTi5B1 master alloys.
Keywords: Aluminium casting alloys; Master alloys applied for refining of the structure; AlTi5B1 master alloy analysis